Recommendations for assigning symbols and names to Neurospora crassa genes now that its genome has been sequenced. - Heather M. Hood; Alan Radford; Matthew S. Sachs (Fungal Genetics Reports, 2008)
Originally, Neurospora crassa genes were named for their mutant phenotypes or natural variant properties. Genes are now increasingly named on the basis of cross-species sequence similarity. These names may also be supported by predicted or experimentally identified molecular function. As a consequence, N. crassa gene nomenclature in practice is frequently no longer adequately covered by the established conventions (Perkins et al. 2001). Here we provide additional nomenclature guidelines relevant to these new circumstances, and some general guidelines for providing information on the identity of N. crassa genes in scientific communications.